2008
DOI: 10.1038/sj.bdj.2008.1043
|View full text |Cite
|
Sign up to set email alerts
|

An audit of the level of knowledge and understanding of informed consent amongst consultant orthodontists in England, Wales and Northern Ireland

Abstract: The results of this audit indicate certain key areas of deficiency in the knowledge and understanding of informed consent amongst consultant orthodontists. The findings provide an opportunity for all clinicians to improve their education and therefore their potential to comply with both the ethical obligation and the legal requirement of gaining valid consent before the start of any treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…The issue of obtaining informed consent prior to treating children can be difficult [20] . It was therefore encouraging to see that nearly 80% of respondents in the current study believed in obtaining consent for a disabled child/child patient and only 15% reported that they did not obtain such informed consent for children.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of obtaining informed consent prior to treating children can be difficult [20] . It was therefore encouraging to see that nearly 80% of respondents in the current study believed in obtaining consent for a disabled child/child patient and only 15% reported that they did not obtain such informed consent for children.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of correct answers is slightly better than in other authors. Chate shows that the average percentage of correct answers in the study on dentists was 57% and was lower in the ques tions on the information given to patients and the ways of verification how the information was understood [6].…”
Section: Discussionmentioning
confidence: 94%
“…We did not find any work analyzing legal awareness of al lergists and pulmonologists. Most papers presents the idea of doctors' awareness and the way of obtaining a conscious consent in the diagnostic and therapeutic process [5][6][7][8][9]. Some works deal with the problem of gathering all nec essary information and the quality of the doctor-patient communication process [9].…”
Section: Discussionmentioning
confidence: 99%
“…The KMA can be used as a tool to determine the SWOT to an organization and to assist the organization in improving its practices to best achieve its goals. In general, KMAs are important to achieve the following goals: defining the opportunities and threats as well as the strengths and weaknesses of the organization for KM purposes, 8,11,43 locating the knowledge resources, 16,20,44,45 determining and analyzing the appropriate flow of knowledge, 9,11,13,25 enhancing individuals' awareness regarding the sharing of their knowledge and enhancement of their relations with other organization members, 16,46 preparing a knowledge map for the organization, 9,11,13,20,44 creating a sense of ownership in individuals with respect to the KM center, 16 enhancing individuals' awareness regarding KM and its importance, 47 providing an opportunity to improve individuals' training in various fields, 48 presenting suggestions on the techniques, mechanisms and tools of KM, 16,42 preparing a knowledge inventory, 11,13,45 determining the key knowledge processes, 8,11,20,44 defining the main factors and indexes for the evaluation of the KM implementation, 8 encouraging individuals to think about the type of knowledge that they require, 16 presenting KM strategies, 8,11,16 analyzing the knowledge network and social network of knowledge, 11 preventing duplicated tasks, 13 designing a knowledge-based system and developing semantic Web sites, 49 preparing the necessary platforms for the development of the KM center, 16,49 guaranteeing the successful execution of KM programs, 11,16,…”
Section: Resultsmentioning
confidence: 99%